Membangun Mimpi Perempuan Desa Sekarwangi Melalui Pelatihan UMKM - Untari, Dhian Tyas; Hutahaean, Erik Saut H; Khasanah, Fata Nidaul (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Through previous survey and observation activities, the main problems that can be identified are as follows; lack of understanding about how to form a business for women in Sekarwangi, Cibadak District, Sukabumi, lack of understanding regarding product development and lack of understanding regarding digital marketing. PKM activities involve several women in Sekarwangi Village, Cibadak District, Sukabumi. To achieve the activity objectives, several steps will be taken as follows; initial observations to inventory needs, provide training related to the formation of a business entity and prepare a marketing plan. Based on these activities, it can be concluded that women have their own positioning in the family economy. Empowering women means giving families access to improve the economic level and welfare of families at a micro level and society at a macro level. In this activity, input was also received that the community needs more help from academics and practitioners to develop the businesses they have been involved in and build new businesses, develop their ideas and abilities.